The Eternal City : A History of Rome in Maps - Maier, Jessica (University of Chicago Press, 2020)
Intro -- Contents -- Introduction: Rome as Idea and Reality -- Further Reading -- Chapter One: Rome Takes Shape -- Rome before Rome -- A Walled City -- Urban Districting -- Further Reading -- Chapter Two: Rome of the Caesars -- Destination Rome -- An Incomplete Puzzle -- Making Sense of the Shattered Past -- Filling in the Gaps -- A Model City -- Further Reading -- Chapter Three: Rome of the Popes -- Sacred Buildings and Secular Symbols -- The Medieval Cityscape -- Pathos and Wonder -- Further Reading -- Chapter Four: Rome Reborn -- A City Ready for Its Close-Up -- The City Seen through a Wide-Angle Lens -- The City Measured -- A Panoramic View of Urban Revitalization -- Further Reading -- Chapter Five: Rome of the Scholars -- Archaeology in Its Infancy -- An Ancient Roman Theme Park -- A Ghostly Fantasy -- Further Reading -- Chapter Six: Rome of the Saints and Pilgrims -- The Way of the Faithful -- Scenes from a Pilgrimage -- A Pilgrimage Map for the Modern Era -- Further Reading -- Chapter Seven: Rome of the Grand Tourists -- Rome as Theater -- The Origins of the Tourist Plan -- Rome Surveyed -- A Panoramic Vision -- Further Reading -- Chapter Eight: Rome of the Mass Tourists -- The Guidebook Impresario's Rome -- Rome for a Rather Important Woman Traveler -- Rome in Your Pocket -- Rome for Italian Tourists -- Further Reading -- Chapter Nine: Rome Enters the Modern Age -- 2,500 Years in, a Master Plan for Rome -- When Trams Ruled Rome -- An Olympic City, and a New Beginning -- Further Reading -- Chapter Ten: Rome Past, Present, and Future -- Rapid Transit for a Rapidly Changing City -- A Master Plan for the Third Millennium: (Un)sustainable Rome -- Further Reading -- Acknowledgments -- Index.